Case Report: Sustained complete remission on combination therapy with olaparib and pembrolizumab in BRCA2-mutated and PD-L1-positive metastatic cholangiocarcinoma after platinum derivate - Zhou, Taotao; Mahn, Robert; Möhring, Christian; Sadeghlar, Farsaneh; Meyer, Carsten; Toma, Marieta; Kreppel, Barbara; Essler, Markus; Glowka, Tim; Matthaei, Hanno; Kalff, Jörg C.; Strassburg, Christian P.; et al. (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) still has a poor prognosis and remains a major therapeutic challenge. When curative resection is not possible, palliative systemic chemotherapy with gemcitabine and platinum derivate as first line followed by a 5-FU doublet combination as second line is the standard therapy. Recently, targeted therapy and immunotherapy have rapidly emerged as personalized therapeutic approaches requiring previous tumor sequencing and molecular profiling. BRCA mutations are well-characterized targets for poly (ADP-ribose) polymerase inhibitors (PARPi). However, BRCA gene mutations in CCA are rare and few data of PARPi in the treatment of CCA are available. Immunotherapy with programmed death receptor-1 (PD-1) has been shown to be effective in combination with chemotherapy or in PD-L1 positive CCA. However, data from immunotherapy combined with targeted therapy, including PARPi, are lacking. In this report, we present the case of a male patient with PD-L1 positive and BRCA2-mutated metastatic intrahepatic cholangiocarcinoma, who was treated with a combined therapy with PARP (PARPi), olaparib, and a PD-1 antibody, pembrolizumab, as second line therapy after gemcitabine/platinum derivate failure. Combined therapy was able to induce a long-lasting complete remission for over 15 months. The combined therapy was feasible and well tolerated. Only mild anemia and immune-related thyroiditis were observed, which were easily manageable and did not result in discontinuation of olaparib and pembrolizumab. Conclusion: The presented case showed substantial clinical activity of a combination with olaparib/pembrolizumab in advanced BRCA2-mutated CCA. Thus, identifying targetable molecular signatures and combinations of targeted therapies with immunotherapy reveal a promising strategy to effectively treat patients with cholangiocarcinoma and should be considered after failure of standard chemotherapy.